Clinical characteristics and outcomes of the multisystem inflammatory syndrome in children (MIS-C) following COVID-19 infection in Iran: A multicenter study. - Fereshteh Rostami-Maskopaee; Fani Ladomenou; Seyedeh-Kiana Razavi-Amoli; Mohammad Reza Navaeifar; Azin Hajialibeig; Leila Shahbaznejad; Fatemeh Hosseinzadeh; Behzad Haghighi Aski; Ali Manafi Anari; Mohsen Mohammadi; Mohammad Bagher Rahmati; Eslam Shorafa; et al. (PLoS ONE, 2022)
Objectives This study aimed to assess the clinical characteristics, treatment and outcomes of the multisystem inflammatory syndrome in children (MIS-C) following COVID-19 in five different geographical regions of Iran. Methods In this multicenter observational study, patients <21 years were included between March 2020 and October 2021. By Disease Control and Prevention (CDC) checklist, demographic characteristics, comorbidities, clinical signs and symptoms, laboratory and radiology findings, and treatment were collected. Statistical analysis was using Chi-square and t-test in STATA14. Results In total 225 patients with median age of 55 (26-96) months were included that 59.56% boys. 57.33% were admitted to the PICU with a median of 7 days (4-10). 95.56% of patients were discharged with recovery and the rest died. All of the patients in our study were included based on the MIS-C criteria. However, some patients had Kawasaki symptoms, so we compared the clinical and epidemiological characteristics of the two groups. Conjunctival injection, cervical lymphadenopathy>1.5 cm diameter, and strawberry tongue in Kawasaki-like MIS-C patients were higher than of MIS-C patients, and this difference was significant(p<0.001). The most common comorbidity was obesity (24.86%). Most patients tested for COVID-19 and about 60% of the patients had a positive test by serology or reverse transcription-polymerase chain reaction (RT-PCR). Gastrointestinal (88.89%) and hematologic signs (84.44%) were most common. Most drugs used in patients were IVIG and steroids. 88.07% and 61.29% of the patients had at least one problem in echocardiography and lung CT, respectively. Conclusions The best outcome was seen in patients who were treated with both IVIG and steroids on the first days of admission. Myocarditis was common in two groups of patients. According to most patients had echocardiography abnormal, screening of heart function is recommended for patients.